Pendaftaran Tanah Sistematis Lengkap, Efektifkah? - Auliah Ambarwati (Jurnal Ilmiah Dinamika Hukum, 2021)
The purpose of this study is to analyze the extent of the application of the land registration process and the factors that influence the application of land registration. This research method uses an empirical normative approach supported by a case approach. The results showed that in the implementation of complete systematic land registration so far is still not effective, in terms of technical and administrative where there are still many errors found on the picture or map on the citizen's certificate either switched or wrong on size. Then the factors that affect the complete systematic land registration are the Procedure and Mechanism Factors as well as the Resource Factors of the Implementing Officer. Keywords: Effectiveness, Procedure, Land Registration